VERBAL EXPRESSION OF THE CONCEPTS OF “HEART” AND “YURAK” (IN COMPARISON BETWEEN ENGLISH AND UZBEK LANGUAGES) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article investigates the semantic and cultural nuances embedded in the verbal expressions of "heart" in English and "yurak" in Uzbek. While both terms broadly denote a central organ associated with life, their linguistic manifestations extend far beyond the physiological, encompassing rich metaphorical landscapes related to emotion, courage, essence, and intellect. Through a comparative analysis, this study aims to delineate the similarities and divergences in how these concepts are utilized in idiomatic expressions, proverbs, and everyday language within their respective linguistic and cultural contexts. The research employs a contrastive linguistic approach, drawing on corpus linguistics for data collection and semantic field theory for analysis.